2021
DOI: 10.1002/bit.27990
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of process analytical technologies for biologics

Abstract: The application of process analytical technology (PAT) for biotherapeutic development and manufacturing has been employed owing to technological, economic, and regulatory advantages across the industry. Typically, chromatographic, spectroscopic, and/or mass spectrometric sensors are integrated into upstream and downstream unit operations in in-line, on-line, or at-line fashion to enable real-time monitoring and control of the process. Despite the widespread utility of PAT technologies at various unit operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…With the exception of physical parameters, such as pH, temperature and dissolved oxygen, that are already controlled automatically, most biological parameters like cell count, viability, nutrient, and metabolite concentrations are only measured at-line once or twice a day. This makes process control difficult and increases the risk of batch failure ( Gillespie et al, 2022 ; Reyes et al, 2022 ). Various studies have investigated how Raman spectroscopy can be used as a PAT tool for on-line measurement of glucose and how a control loop for this parameter can be established.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of physical parameters, such as pH, temperature and dissolved oxygen, that are already controlled automatically, most biological parameters like cell count, viability, nutrient, and metabolite concentrations are only measured at-line once or twice a day. This makes process control difficult and increases the risk of batch failure ( Gillespie et al, 2022 ; Reyes et al, 2022 ). Various studies have investigated how Raman spectroscopy can be used as a PAT tool for on-line measurement of glucose and how a control loop for this parameter can be established.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Additionally, the authors also identified methods aimed at monitoring culture metabolic status as having a high business value in production bioreactors. [ 22 ] It aligned with our previous work, which demonstrated the capacitance spectra as a multi‐attribute analytical tool that contains important early cell death information. [ 13 ] Multiple apoptosis‐related cellular changes may result in the capacitance spectral shape change.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous DSP processing, where there is a constant fluid transfer between unit operations, would seem to benefit naturally from a PAT approach. A recent survey of the BioPhorum Development Group, “PAT monitoring and Control”, representing several biopharmaceutical manufacturers, suggests that PAT implementation has the highest business value for the Protein-A capture and subsequent polishing chromatography steps as compared to other unit operations [ 71 ]. Understandably, much emphasis has been placed on incorporating PAT into the Protein-A capture chromatography step, given its process importance and the high resin cost in the context of antibody DSP.…”
Section: Process Analytical Technologiesmentioning
confidence: 99%